Effects of flaxseed extract on skin wound healing in animal model - Abdul Jabbar, Omar; Kashmoola, Muhannad Ali; Mustafa Al-Ahmad, Basma Ezzat; Mokhtar@Makhtar, Khairani Idah; Muhammad, Siti Aeshah @ Naznin; Abdul Rahim, Roslina; Nazri, Aliah (2019)
INTRODUCTION Wound healing is a complex process which requires special factors and condition. It includes phases such as cell migration, extracellular matrix deposition, remodeling, and angiogenesis. Drugs which accelerate wound healing are expanded, particularly herbal drugs which mainly safe and effective.